Physicochemical and Sensory Evaluation of Mango Squash Utilizing Chemical Preservatives During Storage - Awais, Muhammad; Sajid, Aimen; Muhammad, Ali; Wisal, Shakoor; Shabbir, Hassan; Khan, Shahab; Kalim Ud Din; Madiha; Khan, Niaz Ali (Indus Journal of Bioscience Research, 2025)
This study assessed the physiochemical, sensory characteristics, and storage stability of mango squash with preservatives. Total four squash samples were made which were named as T₀ (Control), T₁ (Sodium Benzoate), T₂ (Potassium metabisulphite) and T₃ (Potassium metabisulphite + Sodium Benzoate). They were packaged in plastic bottles. All samples were sealed properly and stored at room temperature. Samples were analyzed at seven days interval physiochemically (pH, total soluble solids, % titratable acidity and ascorbic acid), and for sensory characteristics (color, flavor and overall acceptability) for a total period of two months. Results clearly showed that storage interval and preservatives had significant effect on physiochemical and organoleptic characteristics. All the treatments indicated a decreasing trend for ascorbic acid, pH, color, flavor and overall acceptability while increasing trend for total soluble solids and titratable acidity (%) during storage period. Total soluble solids increased maximum in T₀ (24.6%) and minimum in T₂ (3.1%). Increase in total soluble solids may be due to hydrolysis of polysaccharides. pH decreased maximum in T₀ (18.8%) and minimum in T₂ (3%). Decrease in pH of mango squash may be due to break down of pectic substances into pectic acid. Ascorbic acid decreased maximum in T₀ (56%) and minimum in T₂ (11%). Decrease in ascorbic acid content is due to presence of oxygen product and other cause is head space in the product packaging. Acidity increased maximum in T₀ (47.5%) and minimum in T₂ (9%). Increase in acidity might be due to high storage temperature and formation of acidic compounds by degradation and oxidation of reducing sugars. Color, flavor, and overall acceptability scores declined most in T₀ and least in T₂ due to higher pulp, sugar, and acid concentrations in T₂, which slowed Maillard reaction and quality deterioration.